Interspecies Electron Transfer via Hydrogen and Formate Rather than Direct Electrical Connections in Cocultures of Pelobacter carbinolicus and Geobacter sulfurreducens - Rotaru, Amelia-Elena (American Society for Microbiology, 2012)
Direct interspecies electron transfer (DIET) is an alternative to interspecies H(2)/formate transfer as a mechanism for microbial species to cooperatively exchange electrons during syntrophic metabolism. To understand what specific properties contribute to DIET, studies were conducted with Pelobacter carbinolicus, a close relative of Geobacter metallireducens, which is capable of DIET. P. carbinolicus grew in coculture with Geobacter sulfurreducens with ethanol as the electron donor and fumarate as the electron acceptor, conditions under which G. sulfurreducens formed direct electrical connections with G. metallireducens. In contrast to the cell aggregation associated with DIET, P. carbinolicus and G. sulfurreducens did not aggregate. Attempts to initiate cocultures with a genetically modified strain of G. sulfurreducens incapable of both H(2) and formate utilization were unsuccessful, whereas cocultures readily grew with mutant strains capable of formate but not H(2) uptake or vice versa. The hydrogenase mutant of G. sulfurreducens compensated, in cocultures, with significantly increased formate dehydrogenase gene expression. In contrast, the transcript abundance of a hydrogenase gene was comparable in cocultures with that for the formate dehydrogenase mutant of G. sulfurreducens or the wild type, suggesting that H(2) was the primary electron carrier in the wild-type cocultures. Cocultures were also initiated with strains of G. sulfurreducens that could not produce pili or OmcS, two essential components for DIET. The finding that P. carbinolicus exchanged electrons with G. sulfurreducens via interspecies transfer of H(2)/formate rather than DIET demonstrates that not all microorganisms that can grow syntrophically are capable of DIET and that closely related microorganisms may use significantly different strategies for interspecies electron exchange.